Academic libraries and the academy strategies and approaches to demonstrate your value, impact, and return on investment - Britto, Marwin 1964-; Kinsley, Kirsten (Association of College and Research Libraries, a division of the American Library Association, 2018)
"Academic Libraries and the Academy is a thorough collection of best practices, lessons learned, approaches, and strategies of how librarians, library professionals, and others in academic libraries around the world are successfully providing evidence of their contributions to student academic success and effectively demonstrating their library's value and worth to institutional administrators and stakeholders. Forty-two case studies are divided into four sections...from beginning assessment work through assessment activities that are more difficult to measure and generally more time- and resource-intensive...to provide practicable ideas and effective strategies for all levels of experience, assessment skills, stages of implementation, and access to resources"...